Symbolic Integration I Transcendental Functions - Bronstein, Manuel (Algorithms and Computation in Mathematics ;, 2005)
This first volume in the series "Algorithms and Computation in Mathematics" is destined to become the standard reference work in the field. Manuel Bronstein is a leading expert on this topic and his book is the first to treat the subject both comprehensively and in sufficient detail - incorporating new results along the way. The book addresses mathematicians and computer scientists interested in symbolic computation, developers and programmers of computer algebra systems as well as users of symbolic integration methods. Many algorithms are given in pseudocode ready for immediate implementation, making the book equally suitable as a textbook for lecture courses on symbolic integration. This second edition offers a new chapter on parallel integration, as well as a few comments on obtaining continuous antiderivatives and additional exercises. From the Reviews "The goal of this well-written book is to present the state of the art in the domain of "integration in finite terms". ... Both aspects of the work, mathematics and implementation, are present in the book. Moreover, Bronstein has chosen a good level of detail, and in such a way that he only deals with the case of transcendental functions. ..." J.M.Ollagnier, Mathematical Reviews 2002 "... It makes an excellent textbook for courses in computer algebra. It contains many exercises and the algorithms are presented in pseudocode, which is easy to implement in any computer algebra system. For those interested in symbolic integration it will become the standard reference." N.A.van Arkel, Medelingen van het wiskundig genootschap 1998 "... The writing is excellent, and the author provides a clear and coherent treatment of the problem of symbolic integration of transcendental functions. Each chapter includes several worked examples and a list of additional exercises. Every researcher and teacher in symbolic computation should have access to this book." F.Winkler, Computing Reviews 1997 "My first thought on seeing this book was "I wish I had written it" - it resembles my lecture notes on the subject, but is better and more complete. ... In sum, the book does what it sets out to do, does it well, and should be on the bookshelf of every implementer or teacher." J.Davenport, The SAC Newsletter 2, 1997.